PENERAPAN KETERAMPILAN DASAR MENGAJAR GURU DI SMP MUHAMMADIYAH SONI DAMPAL SELATAN - Nur'asia Asia (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2019)
Teaching and learning interactions teachers often experience obstacles in carrying out their functions. Therefore, it is necessary to have a holistic approach as a continuous effort to improve the quality of the teaching profession, because the quality and professionalism of teachers can reflect the quality of education and teaching itself, the quality of teachers as an illustration of abilities and skills in carrying out their professional duties. Basic teaching skills for teachers can lead to the success of the education and teaching process, both for teachers and students in teaching and learning activities. The purpose of this study was to determine the application of basic teaching skills for Muhammadiyah Soni Middle School teachers and to find out the forms of applying basic teaching skills for Muhammadiyah Soni Middle School teachers. The research method used is a qualitative approach by describing and interpreting the meaning of data about the application of basic teaching skills, then to obtain data in accordance with the problem, data collection techniques are carried out by observation, interviews, and documentation, then the source of data is obtained from the informant consisting of the head schools and teachers selected as informants or resource persons. The results showed that the application of basic teaching skills in SMP Muhammadiyah Soni had been well implemented. Furthermore, the forms of applying the basic teaching skills that teachers do are basic skills using teaching methods including lecture methods, question and answer methods, discussion methods, and recitation or assignment methods.